The princess diaries - Cabot, Meg. (London : Macmillan, 2000)
Fourteen-year-old Mia, who is trying to lead a normal life as a teenage girl in New York City, is shocked to learn that her father is the Prince of Genovia, a small European principality, and that she is a princess and the heir to the throne.
Keywords: Diaries -- Fiction; Fathers and daughters -- Fiction; Identity -- Fiction; Princesses -- Fiction